2011
DOI: 10.1111/j.1462-5822.2011.01721.x
|View full text |Cite
|
Sign up to set email alerts
|

PE_PGRS30 is required for the full virulence of Mycobacterium tuberculosis

Abstract: SummaryThe role and function of PE_PGRS proteins of Mycobacterium tuberculosis (Mtb) remains elusive. In this study for the first time, Mtb isogenic mutants missing selected PE_PGRSs were used to investigate their role in the pathogenesis of tuberculosis (TB). We demonstrate that the Mtb DPE_PGRS30 mutant was impaired in its ability to colonize lung tissue and to cause tissue damage, specifically during the chronic steps of infection. Inactivation of PE_PGRS30 resulted in an attenuated phenotype in murine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 34 publications
4
99
1
Order By: Relevance
“…It has been shown that extensive amounts of PE and PPE proteins are secreted through the ESX-5 system, which plays crucial roles in mycobacterial virulence (65). For example, as an important ESX-5 substrate, PE_PGRS30 is involved in phagosomal maturation arrest and replication in macrophages (66). Although currently these proteins are the subject of very few biochemical and structure-function investigations, they have been implicated in mycobacterial antigenic variation, which can induce strong immune responses in the host and have roles in mycobacterial virulence and pathogenesis (67).…”
Section: Functional Distribution and Analysis Of The Cfpsmentioning
confidence: 99%
“…It has been shown that extensive amounts of PE and PPE proteins are secreted through the ESX-5 system, which plays crucial roles in mycobacterial virulence (65). For example, as an important ESX-5 substrate, PE_PGRS30 is involved in phagosomal maturation arrest and replication in macrophages (66). Although currently these proteins are the subject of very few biochemical and structure-function investigations, they have been implicated in mycobacterial antigenic variation, which can induce strong immune responses in the host and have roles in mycobacterial virulence and pathogenesis (67).…”
Section: Functional Distribution and Analysis Of The Cfpsmentioning
confidence: 99%
“…Genome-wide mutagenesis approaches indicate that most pe and ppe genes are not essential for M. tuberculosis replication either in laboratory culture or in an animal model (18)(19)(20), suggesting functional redundancy among members of the PE and PPE families. However, PE_P-GRS30 has been implicated in M. tuberculosis virulence (21), and several pe and ppe transposon insertion mutants have been identified in screens for genes involved in phagosome maturation arrest (22,23). In addition, several PE proteins have enzymatic activity.…”
mentioning
confidence: 99%
“…For some of these, the mechanism of action is well known: protein tyrosine phosphatase PtpA is a secreted protein able to inhibit both phagosome-lysosome fusion and the recruitment of the macrophage vacuolar-H + -ATPase (V-ATPase) machinery, responsible of phagosome acidification [21]; lipoamide dehydrogenase LpdC is able to bind coronin-1 (TACO) in the presence of cholesterol preventing its loss from the phagosomal membrane [22]; nucleotide diphosphate kinase Ndk is able to dephosphorylate both Rab7-GTP and Rab5-GTP inhibiting their function [23]; secreted acid phosphatase SapA can dephosphorylate phosphotidylinositol 3-phosphate (PI3P) present on phagosomal membranes, a molecule involved in phagosome maturation [24]; finally lipoarabinomannan (LAM) can be incorporated into membrane rafts of the macrophage cell membrane via its glycosylphosphatidylinositol anchor [25], where it is able to inhibit the increase of cytosolic Ca 2+ concentration in macrophages, which is required for the Ca 2+ /calmodulin PI3 kinase cascade essential for the recruitment of the Rab5 effector early endosome autoantigen (EEA1) to the phagosome and consequently for phagosome maturation [26]. Other virulence factors involved in the arrest of phagosome maturation for which the mechanism is still not completely understood are PE_PGRS62 [27], PE_PGRS30 [28], the lipoprotein signal peptidase LspA [29], the accessory secretion system SecA2 [30], the protein kinase PknG [31], the alternative sigma factor SigE [32], the secreted Zn 2+ -dependent metalloprotease Zmp1 [33], and the two component system regulator PhoP [34]. Since a more efficient trafficking might result in better antigen presentation, M. tuberculosis mutant strains unable to arrest phagosome maturation are not only strongly attenuated, but might be more immunogenic and represent valid alternatives to BCG for immunization, as confirmed by the performance of some candidate vaccines, such as a phoP mutant, which recently entered a Phase I clinical trial [35], and a sigE mutant that is still in preclinical development [36].…”
Section: Mtb Surface Componentsmentioning
confidence: 98%